Adenosine A1 Receptor Agonist 2-chloro-N6-cyclopentyladenosine and Hippocampal Excitability During Brain Development in Rats - Fabera, Petr; Parizkova, Martina; Uttl, Libor; Vondrakova, Katerina; Kubova, Hana; Tsenov, Grygoriy; Mares, Pavel (Frontiers in Pharmacology, 2019)
Objective: The adenosinergic system may influence excitability in the brain. Endogenous and exogenous adenosine has anticonvulsant activity, presumably by activating A1 receptors. Adenosine A1 receptor agonist 2-chloro-N6-cyclopentyladenosine (CCPA) may thus bolster anticonvulsant effect, but its action and amount of A1 receptors in different developmental stages is not known. Methods: Hippocampal epileptic afterdischarges (ADs) were elicited in 12-, 15-, 18-, 25-, 45-, and 60-day-old rats. Stimulation and recording electrodes were implanted into the dorsal hippocampus. The A1 receptor agonist 2-chloro-N6-cyclopentyladenosine (CCPA, 0.5 or 1 mg/kg) was administered intraperitoneally 10 min before the first stimulation. Control animals were injected with saline. All rats were stimulated with a 2-s series of 1-ms biphasic pulses delivered at 60 Hz with increasing stepwise intensity (0.05 - 0.6 mA). Each age and dose group comprised 9-14 animals. AD thresholds and durations were evaluated. A1 receptors were detected in the hippocampus in 7-, 10-, 12-, 15-, 18-, 21-, 25-, 32-, and 52-day-old rats. Results: Both CCPA doses significantly increased hippocampal AD thresholds in 12-, 15-, 18-, and 60-day-old rats compared to controls. In contrast, the higher dose significantly decreased AD threshold in the 25-day-old rats. AD durations were significantly shortened in all age groups except for 25-day-old rats where they were significantly prolonged. A1 receptor expression in the hippocampus was highest in 10-day-old rats and decreased thereafter. Significance: The adenosine A1 receptor agonist CCPA exhibited anticonvulsant activity at all developmental stages studied but 25-day-old rats. Age-related differences might be due to development of presynaptic A1 receptors in the hippocampus.